Profiling spermatogenic failure in adult testes bearing Sox9-deficient Sertoli cells identifies genes involved in feminization, inflammation and stress - Barrionuevo Francisco; Chalmel Frédéric; Lardenois Aurélie; Demougin Philippe; Scherer Gerd; Primig Michael (BMC, 2010)
Abstract Background Sox9 (Sry box containing gene 9) is a DNA-binding transcription factor involved in chondrocyte development and sex determination. The protein's absence in testicular Sertoli nurse cells has been shown to disrupt testicular function in adults but little is known at the genome-wide level about molecular events concomitant with testicular break-down. Methods To determine the genome-wide effect on mRNA concentrations triggered by the absence of Sox9 in Sertoli cells we analysed adult testicular tissue from wild-type versus mutant mice with high-density oligonucleotide microarrays and integrated the output of this experiment with regulatory motif predictions and protein-protein network data. Results We report the genome-wide mRNA signature of adult testes lacking Sox9 in Sertoli cells before and after the onset of late spermatogenic failure as compared to fertile controls. The GeneChip data integrated with evolutionarily conserved Sox9 DNA binding motifs and regulatory network data identified genes involved in feminization, stress response and inflammation. Conclusions Our results extend previous observations that genes required for female gonadogenesis are up-regulated in the absence of Sox9 in fetal Sertoli cells to the adult stage. Importantly, we identify gene networks involved in immunological processes and stress response which is reminiscent of a phenomenon occurring in a sub-group of infertile men. This suggests mice lacking Sox9 in their Sertoli cells to be a potentially useful model for adult human testicular failure.